Claudin Loss-of-Function Disrupts Tight Junctions and Impairs Amelogenesis - Bardet, Claire; Ribes, Sandy; Wu, Yong; Diallo, Mamadou Tidiane; Salmon, Benjamin; Breiderhoff, Tilman; Houillier, Pascal; Müller, Dominik; Chaussain, Catherine (Frontiers in Physiology, 2017)
Claudins are a family of proteins that forms paracellular barriers and pores determining tight junctions (TJ) permeability. Claudin-16 and -19 are pore forming TJ proteins allowing calcium and magnesium reabsorption in the thick ascending limb of Henle's loop (TAL). Loss-of-function mutations in the encoding genes, initially identified to cause Familial Hypomagnesemia with Hypercalciuria and Nephrocalcinosis (FHHNC), were recently shown to be also involved in Amelogenesis Imperfecta (AI). In addition, both claudins were expressed in the murine tooth germ and Claudin-16 knockout (KO) mice displayed abnormal enamel formation. Claudin-3, an ubiquitous claudin expressed in epithelia including kidney, acts as a barrier-forming tight junction protein. We determined that, similarly to claudin-16 and claudin-19, claudin-3 was expressed in the tooth germ, more precisely in the TJ located at the apical end of secretory ameloblasts. The observation of Claudin-3 KO teeth revealed enamel defects associated to impaired TJ structure at the secretory ends of ameloblasts and accumulation of matrix proteins in the forming enamel. Thus, claudin-3 protein loss-of-function disturbs amelogenesis similarly to claudin-16 loss-of-function, highlighting the importance of claudin proteins for the TJ structure. These findings unravel that loss-of-function of either pore or barrier-forming TJ proteins leads to enamel defects. Hence, the major structural function of claudin proteins appears essential for amelogenesis.